Who is using snus? - Time trends, socioeconomic and geographic characteristics of snus users in the ageing Swedish population - Norberg Margareta; Malmberg Gunnar; Ng Nawi; Broström Göran (BMC, 2011)
Abstract Background The prevalence of smoking in Sweden has decreased in recent decades, and is now among the lowest in the world. During the same period, the use of Swedish moist oral snuff, a smokeless tobacco called snus, has increased. Few studies have evaluated time trends of the socioeconomic and geographic characteristics of snus users in Sweden. This paper contributes to filling that gap. Methods This study utilized the Linnaeus Database, which links national registers with comprehensive individual data on socioeconomic status (SES) to health data from a large ongoing health survey, the Västerbotten Intervention Programme (VIP). The VIP targets the entire middle-aged population of Västerbotten county at ages 40, 50 and 60 years with yearly cross-sectional surveys including self-reported data on tobacco habits. Time trends of snus use among 92,563 VIP-participants across different areas of residence and smoking groups were investigated graphically. Logistic regression was performed to estimate the associations between SES and geographical variables and current use versus non-use of snus. Results Overall, in parallel to decreasing smoking, the increasing trend of snus use in this middle-aged population continues, particularly in 40-year-olds. In both genders, the highest prevalence of snus use was observed among previous smokers. The prevalence of snus use also increased over time among smokers, and was consistently higher compared to those who had never smoked. Among males - both those who had never smoked and previous smokers - low education (OR 1.21, 95%CI 1.06-1.40 and OR 1.28, 95%CI 1.14-1.43), living alone (OR 1.16, 95%CI 1.07-1.27 and OR 1.13, 95%ci 1.04-1.23), low income and living in rural areas was associated with using snus, while this was not seen among male current smokers. Among women, living alone was associated with using snus irrespective of smoking habits. Among female smokers, the OR for snus use increased with higher education. Conclusions A disadvantaged social profile and also higher prevalence in rural areas is observed among male snus users who had never smoked or were previous smokers. Among male smokers there was no association between SES and use of snus. The prevalence of snus use among women is increasing, but is still considerably lower than that of men. The association between snus and SES characteristics is less pronounced among women, although snus is clearly linked to living alone. These patterns should be taken into consideration in tobacco control policies.